Reactivity patterns of stibine and trisdimethylaminoantimony precursors for chemical beam epitaxial growth and etching - Foord, J; Howard, F; McGrady, G; Davies, G (1998)
The handling and use of stibine in a CBE environment has been investigated and found to be very straightforward, permitting its use as a CBE precursor. Growth studies of GaSb and InSb on GaAs and SiO2 substrates using this precursor are reported. The compound displays a similar surface reactivity pattern to arsine and phosphine, necessitating the use of thermal pre-crackers operating at 750°C. The surface decomposition pathway of trisdimethylaminoantimony on GaAs surfaces has also been investigated and found to be similar to those of the well-characterised Gp III precursors investigated previously. Clean decomposition leading to the formation of Sb surface is seen on GaAs surfaces, although irreversible decomposition to surface carbon and nitrogen is seen in the presence of Al. Etching studies of GaAs by trisdimethylaminoantimony are also presented, and the nature of the desorbing species responsible for the etching process is discussed. © 1998 Elsevier Science B.V. All rights reserved.